Day 1 Mon, August 31, 2020 2020
DOI: 10.2118/200395-ms
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Well Shut-in After Hydraulic-Fracture Treatments on Productivity and Recovery in Shale Oil Reservoirs

Abstract: Water invasion, associated with hydraulic fracturing, often causes hydrocarbon-mobility hindrance, known as water blocking. The effect on productivity is largely dependent on saturation profiles inside fractures and formation matrix. Enhancement to hydrocarbon recovery has been reported in some field cases after shutting in wells for long time periods. Here we conduct numerical-simulation studies to investigate the effect of well shut-in on initial productivity and long-term recovery. We replica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The well shut-in can increase gas flow rates while decreasing water flow rates in water-wet rocks. 62 Eltahan et al 63 investigated the impact of well shut-in on initial productivity and long-term recovery using numerical simulations. They concluded that injecting water into the formation matrix causes fluid redistribution and encourages non-wetting phase mobility, hence increasing hydrocarbon productivity.…”
Section: Influence Of Shut-in Timementioning
confidence: 99%
“…The well shut-in can increase gas flow rates while decreasing water flow rates in water-wet rocks. 62 Eltahan et al 63 investigated the impact of well shut-in on initial productivity and long-term recovery using numerical simulations. They concluded that injecting water into the formation matrix causes fluid redistribution and encourages non-wetting phase mobility, hence increasing hydrocarbon productivity.…”
Section: Influence Of Shut-in Timementioning
confidence: 99%
“…Well shut-in for a specific time after hydraulic fracturing is the technical way to improve the efficiency of liquid utilization. Shut-in time after fracturing is an important factor influencing the utilization efficiency of fracturing fluid [34][35][36]. In this study, the dualmedium single-stage fracturing model was used to study the utilization law of fracturing fluid during shut-in after fracturing and the effect of shut-in time on the efficiency of fracturing fluid utilization.…”
Section: Well Shut-in Timementioning
confidence: 99%
“…As shown in complex fracture (considering nature fractures) system, it has large drainage area and highdrainage efficiency, therefore the cumulative gas and water production will be larger than simple fractures (without considering nature fractures) system. Chen et al [24] used the structured grid near the fracture to simulate the unified flowback of multilayer fracturing; Eltahan et al [25] conducted 3D-reservoir simulation of complex fractured network that intermeshes with formation matrix and studied well shut-in impact on the productivity and recovery of shale oil reservoirs; Wijaya and Sheng [26] conducted a flow-geomechanical model to study the relationship between imbibition and well shut-in; it shows only if imbibition dominated during recovery in shale reservoir, well shut-in tends to improve both the ultimate oil recovery and net present value (NPV); Tao et al [27] designed a water spontaneous imbibition apparatus, though clay mineral content measurement and salt ion concentration diffusion experiment, the optimal shut-in time for type I and type II shale reservoir are 20 days and 15 days, respectively. Wu et al [28] proposed a two-phase flow model considering formation damage caused by clay expansion and gave a semianalytical-solution model based on Laplace transform, but this method is mainly used for production data analysis and prediction of tight gas wells.…”
Section: Introductionmentioning
confidence: 99%